2010
DOI: 10.1902/jop.2010.100148
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Attachment Loss in Chilean Adult Population: First Chilean National Dental Examination Survey

Abstract: The adult population in Chile shows a high prevalence and extension of clinical AL with age, sex, education level, and smoking as the main risk indicators of severe clinical AL in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
37

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 33 publications
(40 reference statements)
2
48
0
37
Order By: Relevance
“…Particularly, chronic periodontitis (with attachment loss ≥3mm) was prevalent in 97% of Chilean adults between 65 and 74 years of age, 69% of which had severe periodontitis (with attachment loss ≥6mm in at least one site) 9 . In México, a study by Borges-Yañez et al 10 found that 28% of a sample of older people experienced moderate periodontitis (with attachment loss ≥4mm).…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…Particularly, chronic periodontitis (with attachment loss ≥3mm) was prevalent in 97% of Chilean adults between 65 and 74 years of age, 69% of which had severe periodontitis (with attachment loss ≥6mm in at least one site) 9 . In México, a study by Borges-Yañez et al 10 found that 28% of a sample of older people experienced moderate periodontitis (with attachment loss ≥4mm).…”
Section: Periodontal Diseasesmentioning
confidence: 99%
“…Entre estos sujetos, observamos incluso algunos menores de 35 años (Tabla 2). Como se ha visto en los artículos antes citados, en nuestro país la presentación precoz de pérdida de inserción se describe incluso en adolescentes (4,5,6,7) . Al realizar pruebas de asociación entre severidad/extensión y variables socio-demográficas como sexo, edad, tabaquismo y escolaridad de los sujetos de este estudio, se encontraron diferencias significativas para edad y sexo, pero no para escolaridad y tabaquismo.…”
Section: Test De La Probabilidad Exacta De Fisherunclassified
“…Al realizar pruebas de asociación entre severidad/extensión y variables socio-demográficas como sexo, edad, tabaquismo y escolaridad de los sujetos de este estudio, se encontraron diferencias significativas para edad y sexo, pero no para escolaridad y tabaquismo. Tomando en cuenta estos últimos, que son factores de susceptibilidad/ riesgo reconocidos, creemos que en el caso de la escolaridad hubo una tendencia con un p cercano a la significancia estadística (p=0,062), por lo tanto de ampliarse el número de sujetos, podría confirmarse esta asociación, tal como se ha observado en estudios epidemiológicos realizados en Chile y en Latinoamérica (4,5,6,7) . En cuanto a la variable tabaquismo, era de esperar que no se observara asociación dado que había pocos sujetos fumadores en este estudio con bajo número de cigarrillos fumados por día.…”
Section: Test De La Probabilidad Exacta De Fisherunclassified
See 1 more Smart Citation
“…7 In addition, the global burden of oral diseases is also relatively high in elderly, particularly periodontal disease, which was remained at higher levels in Asia. [8][9][10][11][12] The chronic destruction of periodontal tissue which presented as the major cause of tooth loss was proven to have an association with CVD. [13][14][15] Periodontal pathogens were found to be the possible association between periodontal disease and atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%